MODERN PEDAGOGICAL TECHNOLOGIES FOR ORGANIZING INDIVIDUALIZED LEARNING IN PRIMARY SCHOOL - Shoira Chariyevna Djalilova (Modern American Journals, 2025)
This article explores the application of modern pedagogical technologies for organizing individualized learning in primary school. Individualized learning is considered a central strategy to enhance the quality of education by addressing the cognitive, psychological, and developmental characteristics of each student. The study examines a range of contemporary approaches, including differentiated instruction, modular learning, project-based methods, digital tools, and game-based strategies, emphasizing their role in fostering motivation, independence, and creativity. The article also analyzes the challenges teachers face in implementing these technologies, such as limited resources and insufficient methodological preparation, and offers recommendations for improving pedagogical practice. The findings highlight that integrating modern technologies into primary education supports the development of flexible, student-centered learning environments that prepare children for future academic success and personal growth.
Keywords: Pedagogical technologies, individualized learning, primary school, differentiated instruction, project-based learning, digital tools, game-based strategies.